54.4k views
1 vote
Solve the following quadratic equation by using the quadratic formula.

-2x^2 - 3x + 4 = 0

(Answers are in photo)

10 points!!!
please explain how you got your answer.

Solve the following quadratic equation by using the quadratic formula. -2x^2 - 3x-example-1
User Vinnydiehl
by
5.7k points

1 Answer

2 votes

Answer:

B.
(-3)/(4)±
(√(41) )/(4)

Explanation:

First, substitute the equation into the quadratic formula.


x=\frac{b+-\sqrt{(b^(2) )-4(a)(c)} }{2a}

x=
(-3+-√((3)^2-4(-2)(4)) )/(4)

Solve for x.

x=
(-3+-√(9+32) )/(4)

x=
(-3+-√(41) )/(4)

The answer is x=
-(3)/(4)±
(√(41) )/(4)

User Pablo Retyk
by
5.6k points